Pengaruh Infeksi Beberapa Jenis Virus Terhadap Penurunan Hasil Produksi Tanaman Tomat ( Solanum lycopersicum Mill.) Di Dusun Marga Tengah, Desa Kerta, Kecamatan Payangan, Kabupaten Gianyar - MAHENDRA, IDA BAGUS GEDE; PHABIOLA, TRISNA AGUNG; YULIADHI, KETUT AYU (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2017)
Effect of Virus Infection Several Types of Decreased Production Plant Tomato (Solanum lycopersicum Mill ) in Dusun Marga Tengah, Kerta Village, Payangan District, Gianyar Regency The purpose of this research is to know the how much yield loss due to virus infection on tomato plants as well as knowing viruses that attack tomato plants with symptoms of mosaic and yellow. This study was conducted from October 2016 through December 2016 held at Dusun Marga Tengah, Payangan, Gianyar. Activities undertaken during the study was the observation of symptomatic plant virus, harvesting, sampling symptomatic mosaic, yellow and serology ELISA (Enzyme Link Immunosorbent Assay). Field observations show that plants with mosaic symptoms have a higher incidence of the disease (21.75%) and plants with symptoms of yellow (13.17%). Tomato plants with mosaic symptoms resulted in an average yield of 498.54 grams with the highest rate of loss of 82.73% and a yellow tomato plants with symptoms caused average crop yield of 1672.50 grams with a loss rate of yield of 44.48%. The results of serologic testing by ELISA of leaf samples of tomato plants with mosaic symptoms were positively infected TMV ( Kutu Putih ) and leaf samples of tomato plants with symptoms of infection PepYLCV (Pepper yellow leaf curl virus) positive yellow.